The Presence of Modernist Architecture in Government’s educational Buildings at Lefkosa - Maryam Iranfar (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Modernist architecture movement of the buildings in any city reflects the modernity of that city. Lefkosa as a modern city faced many conflicts in the last century. The governmental buildings illustrate how modernism in architecture was defined and reflected in the buildings of the city. The aim of this paper is to explore the modernism movement in architecture influence on educational governmental buildings in Lefkosa for the first half in the 20th century. The paper focuses on the ideas and experiences of modernist architects in the first half of the 20th century to apply modernism elements and relationship between architecture form and functionalism in governmental buildings. Methodology framework elucidated to conduct the subject. Two School buildings have been selected from the first half of the twentieth century in Lefkosa as case studies for modernist architecture. ‘Lefkosa türk lisesi’ designed by ‘Ahmet Vural Bahaedden’, which was one of the famous modernist architects in Cyprus and ‘sehit Ertugrul Ilkokulu’. The buildings architectural elements analyzed in both schools to demonstrate the relationship between site, interior space, functionality and environmental response, based on using their modern material and character. The paper concluded that the educational buildings hold strong elements of the modernist architecture in Lefkosa and demonstrate how the elements of modernism were involved functionally in the design. The findings contribute useful evidence about the existence of modernism philosophy in architecture in Lefkosa in the first half of the twentieth century.